The Lone Mother Resilience Project: A Qualitative Secondary Analysis - Watters, Elizabeth C.; Caragata, Lea; Cumming, Sara (DEU, 2018)
Although qualitative secondary analyses are conducted across the social sciences, supra-assorted analyses that involve both the re-use of existing data and the collection of new, primary data are relatively uncommon. Additionally, discussions regarding qualitative secondary analysis have tended to ignore the re-use of researchers' own data (i.e., auto-data). Thus, with this article, we aim to contribute to this discussion by providing an example of a supra-assorted analysis in which we re-used data from one of our previous studies, Lone Mothers: Building Social Inclusion. This earlier, longitudinal study was conducted with 104 poor lone mothers across Canada. We supplemented this dataset with data from three focus groups and 20 semi-structured interviews engaging a total of 38 lone mothers. Both studies were informed by a feminist and social inclusion lens, and recruited a diverse sample of women in three cities across the country: Vancouver, British Columbia; Toronto, Ontario; and St. John's, Newfoundland. In addition, most of the lone mothers who participated in the secondary analysis had also been involved in the original study as interviewees and/or research assistants. We conclude the article by discussing the strengths and limitations of, and lessons learned from, the secondary study's design. Obwohl qualitative Sekundäranalysen in den Sozialwissenschaften mittlerweile breite Anwendung finden, sind gemischte Studien, in denen bereits existierende und neu erhobene Daten genutzt werden, vergleichsweise selten. Ebenso wird die (Wieder-) Verwendung von eigenen Forschungsdaten kaum diskutiert. Zur Schließung dieser Lücke wollen wir mit dem hier vorgestellten Artikel beitragen. Zum einen wurden in die Analyse Daten des bereits abgeschlossenen "Lone Mothers: Building Social Inclusion"-Projekts einbezogen, eine Längsschnittstudie, in deren Verlauf wir 104 alleinstehende Mütter aus eher armen Verhältnissen einbezogen hatten. Diese Daten wurden durch Daten ergänzt, die aus drei Fokusgruppen und 20 ...